Building Construction, Road Works and Waste Management: Impact of Anthropogenic Actions on Flooding in Yenagoa, Nigeria - Warebi G. Brisibe; Ibama Brown (International Journal of Architectural Engineering Technology, 2020)
Floods are generally seen as natural occurrences with other underlying causal factors. These factors are both natural and anthropogenic in nature and often induce or exacerbate flood episodes in the environment. As it were, while some of these factors stem from natural ecological cycles, others are engendered by accumulated anthropogenic actions or inactions. This study aims to examine three independent documents comprising of two technical reports commissioned by the Bayelsa State government in Yenagoa and contiguous neighborhoods and narratives from a PhD flood research with a view to understanding the nature and dynamics of anthropogenic actions causing flooding in Bayelsa State. The objectives include; a systematic review of the government commissioned technical reports on floods in Yenagoa and other related documents; identify and highlight both natural and anthropogenic causes of flooding in the study area; recommend an appropriate course of action. The study adopted direct personal observation, photography and secondary data analysis to obtain data. Findings from the combination of these documents highlight some of the deliberate human actions and/or inactions taken by both Government and private developers regarding incidents of flooding within the Yenagoa Metropolis. Based on the document’s review, three key anthropogenic actions were identified; building construction and other physical development activities, waste management and drainage systems and public infrastructure development. Specific recommendations such as the adoption of a holistic approach towards harmonized flood data management framework, effective implementation of such policies to tackle these identified challenges, undertake EIA, hydrologic and hydrographic studies, as well as base line studies before embarking on any developmental projects, desilting of clogged drainage culverts and proper alignment of road projects to reduce incursion and subsequent impediment of free flow of runoffs were made.